Detection and tracking for radar simulation using MATLAB - Almarghani, Khaled Ali. O. (2012)
The objective of the project is to simulate the real time Radar detection and tracking operations using MATLAB software. Radar system use modulated waveforms and directive antennas to transmit electromagnetic energy into a specific volume in space to search for targets. Objects (targets) within a search volume will reflect portions of this energy (radar returns or echoes) back to the radar. These echoes are then processed by radar receiver to extract target information such as range. Velocity, angular position, and other target identifying characteristics. The project mainly concentrates on the radar displays and different radar types to collect the information of the flying objects, such as the range, speed, distance, angles. The display types are A-scope, B-scope, C-scope, PPI, and RHI, which are used in modern radars. While others are either obsolete or are found only in very specialized applications. Signals displayed on these scopes can be raw video, synthetic video (detected video) or computer-generated symbols. The radar types consider in the project are CWT (Continuous Wave Transmission), Pulse, Doppler, and MTI (Moving Target Indicator). For each display, all the values related to the object are calculated in different patterns and graphs for the corresponding formulated values and angles.